Lateral thinking: a textbook of creativity - De Bono, Edward (Penguin, 1970)
Through a series of special techniques, in groups or working alone, Edward de Bono shows us how to look at problems from a variety of angles and in so doing offer up solutions that are as ingenious as they are effective. After reading this book you will become a much more productive and formidable thinker.